Evaluation of Small Vessel Disease by Advanced Brain Imaging - Atul Khajuria; Mohammad Younus (International Journal of Cheminformatics, 2024)
Studying and comprehending brain small vessel disease requires extensive imaging. Recent applications of cutting-edge brain imaging techniques have led to the discovery of several significant results. Diffusion-weighted MRI studies have demonstrated the diagnostic accuracy of using clinical features alone or in combination with CT scan results to identify small vessel disease as the underlying cause is suboptimal in patients with acute lacunar syndromes. Acute infarcts caused by small vessel disease may cavitate, meld with abnormalities in the white matter, or even go unnoticed over time, according to follow-up imaging investigations on patients. High-resolution MRI may show intracranial atherosclerosis in larger arteries (which could obstruct penetrating artery orifices and result in small deep infarcts), but it is currently unable to show abnormalities in single penetrating arteries.
Keywords: Cerebral small vessel disease (SVD); computerized tomography (CT); magnetic resonance imaging (MRI); microinfarcts